The Effectiveness of Psychosocial Interventions on Increasing Self-Efficacy for Drug Abusers: Systematic Review - Rahmawati Rahmawati; Achir Yani S. Hamid; Giur Hargiana; Yossie Susanti Eka Putri (Indonesian Journal of Global Health Research, 2025)
Drug abuse can occur an increase in global and national prevalence rates. This is influenced by several factors including the family and community environment, causing several impacts including biological, psychological and social impacts between the psycholoogical impacts of drug abuse, namely the decrease in self-esteem and self-efficacy. Handling of drug users needs to be given in order to increase self-efficacy, nursing care that can be given in the form of Psycosocial Intervention is the application of interventions in the form of rehabilitation therapy, supportive therapy, group therapy, supportive counseling, therapeutic communities, group education, and yoga. Literature search through several databases namely Proquest, Science Direct, Wiley Online Library and Google Scholar in the last 5 years. Search uses english keywords: (1) drug abuse or drug dependence, (2) pshycosocial intervention, (3) self efficacy, (4) self-esteem. There are eight research articles, including three articles using Randomized Control Trials and five other articles using Quasi-Experimental Design. By strengthening knowledge, increasing self defense, providing social support, and improving perceptions about drug users, psychosocial interventions can be an effective intervention in increasing long-term self-efficacy for drug users not to return to addiction.